2018
DOI: 10.1093/jas/sky172
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of direct and maternal genetic parameters for individual birth weight, weaning weight, and probe weight in Yorkshire and Landrace pigs1

Abstract: As a result of selecting for increased litter size, newborn piglets are being born lighter and have a lower chance of survival. Raising fewer pigs to market weight would have a negative impact on the industry and farmer profitability; thus, understanding the genetics of individual growth performance traits will determine whether these traits will play an important role in pig breeding schemes. This study aimed to estimate genetic parameters for individual birth weight (BW), weaning weight (WW), and probe weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 37 publications
(70 reference statements)
7
14
1
1
Order By: Relevance
“…As shown, the heritability estimates of the IBW trait with their associated standard errors were found to be 0.500 (0.013), 0.212 (0.018), 0.322 (0.017), and 0.130 (0.019) per statistical model (Equations (1)-(4)). These results are similar to a recent report [9] when using the full model (Equation (4)) with an estimated IBW heritability in the Yorkshire and Landrace pigs of 0.15 and 0.05, respectively, while including the maternal, common litter, and direct additive effects. Regarding the case of birth weight, it was estimated that the maternal effect, which included the common environmental effect, had a fairly high variance component and, as a result of the likelihood ratio test, the full model (Equation (4)) included all the maternal effects and, hence, was identified to be the most optimal model.…”
Section: Heritability and The Optimized Modelsupporting
confidence: 90%
See 1 more Smart Citation
“…As shown, the heritability estimates of the IBW trait with their associated standard errors were found to be 0.500 (0.013), 0.212 (0.018), 0.322 (0.017), and 0.130 (0.019) per statistical model (Equations (1)-(4)). These results are similar to a recent report [9] when using the full model (Equation (4)) with an estimated IBW heritability in the Yorkshire and Landrace pigs of 0.15 and 0.05, respectively, while including the maternal, common litter, and direct additive effects. Regarding the case of birth weight, it was estimated that the maternal effect, which included the common environmental effect, had a fairly high variance component and, as a result of the likelihood ratio test, the full model (Equation (4)) included all the maternal effects and, hence, was identified to be the most optimal model.…”
Section: Heritability and The Optimized Modelsupporting
confidence: 90%
“…One of the most representative traits is individual birth weight (IBW) in piglets [5][6][7][8], where IBW reflects the individual abilities of the offspring that are affected by genetic factors and the intrauterine nutritional supply. Hence, improving the genetic progress of IBW is crucial for understanding the genetic control of the indicators [9]. However, previous studies have reported that the heritability of the birth weight is low, ranging from 0.09 to 0.21 [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…We evaluated different models to estimate genetic parameters and breeding values of individual dromedary bulls for the birth weight trait. According to the e 2 and − 2 log L data (Alves et al 2018 ), the BLUP1 and BLUP2 models were equally reliable and were more accurate than the ANOVA model. In addition, the difference in maternal genetic effects obtained by two BLUP models was due to the fact that the BLUP1 model did not contain permanent environmental effects, so, the total maternal (genetic + environmental) effect was considered as a genetic influence.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the most suitable model for estimating the parameters, the e 2 values and log-likelihood values (− 2 log L) for the three different models were compared (Bouwman et al 2010;Alves et al 2018).…”
Section: Collection Of Reproductive Data Estimation Of Genetic Parammentioning
confidence: 99%
“…The growth of a pig is determined by the piglet as well as its dam, respectively through effects termed direct and maternal effects (Alves 2015). The trait, as measured, is the phenotypic value of the offspring, but it is composed of at least two components: offspring growth and a maternal effect contributed by the dam.…”
Section: Maternal Effects Estimates In Swinementioning
confidence: 99%